Does religion matter to informal finance? Evidence from trade credit in China. Issue 10 (3rd October 2019) - Cao, Chunfang; Chan, Kam C.; Hou, Wenxuan; Jia, Fansheng
ABSTRACT: Informal finance plays an important role in transitional economies with weak legal institutions, such as China. As a major informal finance instrument, trade credit relies on informal institutions and enforcement. The paper argues that religion enhances the ethical climate in which firms do business, and it predicts that religiosity increases trade credit, in that religion enhances enforcement by increasing non-pecuniary cost and reducing risk-taking. The results based on Chinese non-state listed firms between 2003 and 2013 confirm the prediction that firms located in high-religiosity regions are associated with more trade credit, especially in regions where formal institutions are weak or formal financing channels are limited. Furthermore, the paper shows that religiosity reduces overdue trade credit. Finally, the results are driven by Buddhism, Taoism and Christianity, but not Islam.